Plasmid Profiling and Occurrence of β-Lactamase Enzymes in Multidrug-Resistant Uropathogenic Escherichia coli in Kathmandu, Nepal - Thapa Shrestha U; Shrestha S; Adhikari N; Rijal KR; Shrestha B; Adhikari B; Banjara MR; Ghimire P (Infection and Drug Resistance, 2020)
Upendra Thapa Shrestha,1,2,* Sabnum Shrestha,1,* Nabaraj Adhikari,1,2 Komal Raj Rijal,2 Basudha Shrestha,3 Bipin Adhikari,4 Megha Raj Banjara,2 Prakash Ghimire2 1Kantipur College of Medical Science, Tribhuvan University, Sitapaila, Kathmandu, Nepal; 2Central Department of Microbiology, Tribhuvan University, Kathmandu, Nepal; 3Department of Microbiology, Kathmandu Model Hospital, Kathmandu, Nepal; 4Centre for Tropical Medicine and Global Health, Nuffield Department of Medicine, University of Oxford, Oxford, UK*These authors contributed equally to this workCorrespondence: Komal Raj RijalCentral Department of Microbiology, Tribhuvan University, Kirtipur, Kathmandu, NepalEmail rijalkomal@gmail.comIntroduction: Extended-spectrum β-lactamases (ESBL) among Gram-negative bacteria, predominantly Escherichia coli (E. coli), in Nepal, have been rising. The main objectives of this study were to determine the prevalence of uropathogenic E. coli, antibiotic resistance, ESBLs, ABLs (AmpC type β-lactamases), MBLs (metallo-β-lactamases) and KPCs (Klebsiella pneumoniae carbapenemases) and their correlation with plasmid profiling patterns among patients with urinary tract infections in a tertiary hospital in Kathmandu, Nepal.Methods: The mid-stream urine samples collected from patients were inoculated in cystine–lactose–electrolyte-deficient (CLED) agar plates. E. coli producing ESBLs, ABLs, MBLs/KPC were identified phenotypically using standard microbiological methods. Plasmids were extracted by alkaline lysis method from E. coli isolates and profiled using agarose gel electrophoresis.Results: Out of the total 2661 urine samples, E. coli were isolated in 64.34% (507/788), among which 170 (33.53%) were multidrug-resistant (MDR) isolates. All MDR isolates were resistant to amoxicillin and third-generation cephalosporins but were highly sensitive to imipenem (94.12%, 160/170), amikacin (92.94%, 158/170) and nitrofurantoin (86.47%, 147/170). Among 170 MDR isolates, 78.2% (133/170) were ESBLs, 46.3% (50/170) were AmpC, 11.2% (19/170) were MBL and 0.6% (1/170) were KPC producers. Coproduction of β-lactamases was detected in 24.12% (41/170) of isolates. E. coli isolates showed one plasmid (> 33.5 kb), which was present in all the isolates. Overall, 44 different plasmid profile groups were identified based on molecular weight and number of plasmids. β-Lactamase producers were relatively resistant to the higher number of antibiotics tested (≤ 10) than non-producers (≤ 8), and the number of plasmids were higher in β-lactamase producers (≤ 7) than those in non-producers (≤ 5).Conclusion: The higher prevalence of the ESBLs, AmpCs, KPCs and MBLs along with their coproduction in E. coli isolates highlights the importance of routine surveillance of ESBLs, AmpCs, KPCs and MBLs in microbiology laboratories using various phenotypic methods.Keywords: uropathogenic Escherichia coli, antibiotic resistance, ESBL, extended-spectrum β-lactamases, AmpC type β-lactamases, MBL, metallo-β-lactamases, KPC, Klebsiella pneumoniae carbapenemases